Analisis Jurnal Multimedia Menggunakan Teknik Animasi 2 Dimensi - Sabrina Putri; Muhammad Isnan; Nurhayati; Alwi Haryada; Ali Ikhwan (Jurnal Pendidikan, Sains Dan Teknologi, 2023)
Information and Communication Technology is developing very rapidly. One of the rapidly growing technologies today is Multimedia. Where Multimedia learns about 2-dimensional and 3-dimensional animation techniques. The material is also about animation, video, and others. This multimedia learning media can also be done through power point which is really needed by students in general. The role of information technology in the modern era is very much and maybe it can become the main foundation of science because all information and knowledge has entered the digital era. Starting from the fields of education, military, business, industry to health, they really need technology and information is conveyed, which previously may have been limited, now it can spread widely to all corners of the world using the internet. The use of information technology must also be monitored and guarded so that unwanted use does not occur, even though this information technology has many positive impacts, we must be aware of the negative impacts for the next generation as well.